A cross sectional study on prevalence of depression in late adolescents studying in JSS high schools and colleges in Mysore district - Tiwari, Rajiv Ranjan; D., Sunil Kumar; Bheemaiah, Accamma K. (International Journal Of Community Medicine And Public Health, 2022)
Background: This study aimed to identify factors significantly associated with recent depressive mood concerning health-related behavioral patterns at the individual level, perceived safety in the school environment, and willingness to share concerns with family and social networks. Methods: In the cross-sectional study, a total of 221 middle school students were selected from 5 colleges in Mysuru, Karnataka by probability proportional to size sampling. Beck’s depression inventory and semi-structured questionnaire were used to evaluate the Prevalence of depression and factors associated with depression, respectively. Multivariable logistic regression analysis was conducted to explore the association between Factors and Depression in adolescents Results: 29% of the students reported positive in Depression assessed by the BDI scale. The lifestyle and academic performance were significantly associated with Depression. Moreover, a higher risk of mental health problems was associated with poorer school interpersonal relationships Conclusions: Depression was prevalent among adolescents and highly associated with lifestyle and academic performance. Our findings underscore the pressing need for school administrators to make efforts to improve school interpersonal relationships among adolescents.